Bimbingan Kelompok dengan Teknik Self-Instruction untuk Meningkatkan Self-Regulation Siswa - Bambang Setiawan; M. Solehuddin; Anne Hafina (ILIN Institute, 2019)
Triggered by the importance of self-regulation, then this research was conducted in order to test the effectiveness of group guidance with self-instruction technique in order to enhance self-regulation of the students. Self-regulation is considered as the As card of human personality as it is assumed to be able to strenghten and increase the ability of a person to face the demand of live as well as act as a guide of behaviours of the person himself. In addition, lack of self-regulation will also cause wide range of problems specifically for the students as it may affect the academic achivement of the students themselves. Quantitative approach with quasy-experimental design was used in this research. Meanwhile, the research method used was Nonequivalent Pretest-Posttest Control Group Design. The selection of the sample of the study was by using the purposive sampling technique, the total samples taken were 69 students, 39 students were placed in experimental group and other 30 students were in control group. The study found that in general the profile of the students’ self-regulation was on the moderate category, and empirically the group guidance with self-instruction technique was proven to be able to enhance students’ self-regulation.